Research progress on the N protein of porcine reproductive and respiratory syndrome virus - Zheng, Yajie; Li, Gan; Luo, Qin; Sha, Huiyang; Zhang, Hang; Wang, Ruining; Kong, Weili; Liao, Jiedan; Zhao, Mengmeng (Frontiers in Microbiology, 2024)
Porcine reproductive and respiratory syndrome (PRRS) is a highly contagious disease caused by the porcine reproductive and respiratory syndrome virus (PRRSV). PRRSV exhibits genetic diversity and complexity in terms of immune responses, posing challenges for eradication. The nucleocapsid (N) protein of PRRSV, an alkaline phosphoprotein, is important for various biological functions. This review summarizes the structural characteristics, genetic evolution, impact on PRRSV replication and virulence, interactions between viral and host proteins, modulation of host immunity, detection techniques targeting the N protein, and progress in vaccine development. The discussion provides a theoretical foundation for understanding the pathogenic mechanisms underlying PRRSV virulence, developing diagnostic techniques, and designing effective vaccines.